Mathematical critical thinking ability reviewing from domicile, gender, and adversity quotient - Sartika Putri , Natalia Dinda; Alyani, Fitri (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2023)
Students' mathematical achievement in mathematical critical thinking skills is still in the low category. This study analyses mathematical critical thinking skills based on domicile, gender, and adversity quotient. This research is a qualitative case study. The subjects selected through purposive sampling came from high schools in the Jakarta and Tangerang class XI areas. The data were analyzed using the Rasch Model, namely Winstep through the stages of reduction and categorization, presentation, and conclusion. The results of the study obtained the ability to think critically mathematically based on domicile, the subject of urban domicile was able to meet all indicators of Critical thinking well. Based on gender, subjects of the female and male genders have the same mathematical abilities on critical thinking indicators. According to the adversity quotient, the subject in the subject climber type can solve the problem properly and precisely, and in the camper type the subject can solve the problem precisely however, in the inference indicators the two subjects do not describe the requested graph and are in the dominant camper type, while the quitter type has a low AQ ability with indicators that are met only interpretation.